OS PROCESSOS DE HIGIENE VERBAL E O POLITICAMENTE CORRETO - Piasecka-Till, Aleksandra (Intercâmbio, 2010)
Taking into consideration Fairclough’s (1989,1992) statement that language use (discourse) shapes and is shaped by society, I discuss the concept of "verbal hygiene" (Cameron 1995) and its implications for critiques of "political correctness."